Orbital exenteration in immunodeficiency virus-infected patients - Giles K (Dove Medical Press, 2016)
Kagmeni Giles,1,2 Yannick Bilong,1,2 Nomo Arlette,1,2 Nanfack Chantal,1,3 Bella Assumpta Lucienne1,3 1Eye Department, University of Yaoundé I, 2Yaounde Teaching Hospital, 3Gyneco-Obstetric and Pediatric Hospital, Yaoundé, Cameroon Background: Orbital exenteration (OE) is a disfiguring procedure most commonly performed for locally advanced and potentially life-threatening periorbital malignancies.Methods: We retrospectively reviewed records of 11 consecutive HIV patients who underwent OE for invasive orbital malignancy at our institution from January 2005 to December 2015. Patient demographic and clinic data and histopathology of the tumor were analyzed.Results: There were eight (72.72%) female and three (27.28%) male participants ranging in age from 31 to 52 years with an mean of 39.4 years. Nine patients had been known to be HIV-positive for at least 2 years, and HIV-positive status was revealed at presentation for two patients. The mean CD4 cell count was 154.4 cells/mm3. Histopathological examination showed invasive orbital squamous cell carcinomas in nine patients (81.81%), achromic orbital melanoma in one patient (9.09%), and adenoid cystic carcinoma in one patient (9.09%). None of the patients underwent primary orbital reconstruction. The mean follow-up time was 3.4 months. Only one patient who underwent adjuvant radiotherapy was seen after 12 months.Conclusion: Oculo-orbital malignancies are very aggressive in HIV-positive individuals, especially in untreated patients. Routine screening for suspected ocular surface lesions and early surgical removal of all these lesions could help to avoid the need to perform the radical and disfiguring OE procedure. Keywords: orbital tumors, achromic melanoma, squamous cell carcinoma, HIV